2002
DOI: 10.1038/sj.ejhg.5200816
|View full text |Cite
|
Sign up to set email alerts
|

Linkage disequilibrium and demographic history of the isolated population of the Faroe Islands

Abstract: The isolated population of the Faroe Islands has a history of recent expansion after being limited to a small size for centuries. Such an isolated population may be ideal for linkage disequilibrium mapping of disease genes if linkage disequilibrium (LD) extends over large regions. Analyses of 18 markers on 12q24.3, spanning a region of 4.3 Mb (16 cM), revealed extensive LD in the Faroese population. Maximum LD was found between marker pairs separated by more than 3.8 Mb. The same region had a maximum LD of onl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
29
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 40 publications
(32 citation statements)
references
References 38 publications
3
29
0
Order By: Relevance
“…63,65 Conflicting evidence has, however, been reported regarding the actual degree of homogeneity of isolated populations. 64 A previous study on the Faroese population 25 indicated extensive LD among the 15 markers surveyed. Furthermore, the allelic diversity was smaller, although nonsignificant in the Faroese population compared to outbred populations.…”
Section: Discussionmentioning
confidence: 92%
See 3 more Smart Citations
“…63,65 Conflicting evidence has, however, been reported regarding the actual degree of homogeneity of isolated populations. 64 A previous study on the Faroese population 25 indicated extensive LD among the 15 markers surveyed. Furthermore, the allelic diversity was smaller, although nonsignificant in the Faroese population compared to outbred populations.…”
Section: Discussionmentioning
confidence: 92%
“…Despite lack of evidence for a strong population bottleneck on the Faroe Islands, the population is considered suitable for LD mapping of complex diseases. 25 To avoid bias due to population stratification, it is essential that cases and controls are subsamples of the same panmictic population and share a similar genetic history. Based on Wright's F ST and modelbased clustering analyses, this essential assumption seems valid for our sample of cases and controls.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The Bonferroni correction, which assumes independence between the individual tests, was considered too conservative. As many of the markers are in close proximity, they are likely in LD, 41 and the association tests performed are hence not independent. However, to compensate for multiple testing and reduce the type I error rate, we applied relatively low thresholds in stage 1 and 2.…”
Section: Discussionmentioning
confidence: 99%